Applicability of Modified University of Illinois at Urbana–Champaign Model for Unbound Aggregate Material with Different Water Content. Issue 3 (March 2019) - Lin, Tianshu; Ishikawa, Tatsuya; Luo, Bin
This paper proposes a modified University of Illinois at Urbana–Champaign (UIUC) model to predict permanent deformation behavior of unbound aggregate materials. Most existing models relate permanent deformation to resilient properties, whereas the UIUC model treats shear strength as a critical factor in permanent deformation behavior. Three types of test, monotonic shearing test, cyclic axial loading test, and cyclic axial and shear loading test, were conducted by multi-ring shear apparatus on two kinds of parallel grading aggregate materials, natural crusher-run and recycled crusher-run obtained from demolished concrete structure. Test results demonstrate that shear strength is the core factor in permanent deformation behavior, compared with resilient properties, and principal stress axis rotation (PSAR) greatly increases the permanent deformation. By considering the effect of PSAR on permanent deformation, a new parameter, ( Rs )ave, is added to the conventional UIUC model to modify it. Regression analysis results verify that the modified UIUC model has good applicability for predicting permanent deformation of aggregates with different water contents and stress states, and with and without PSAR. The modified UIUC model builds a relation between test results with and without PSAR. A simple framework is also proposed for predicting permanent deformation in flexible pavement structures based on the modified UIUC model.